Exploring the effects of ventilation and air-conditioned environments, on droplet and airborne transmission of SARS-COV-2 - Deeb, Sinan; Rehan, Haithem; Hamameh, Husam; Schwentner, Ilona; Wolpert, Stephan; Becker, Sven (International Journal of Innovative Research and Scientific Studies, 2023)
To assess the implications of air conditioning and ventilation on droplet and airborne transmission of SARS-COV-2, several scientific research databases were searched and cross-referenced. Then, an analysis was conducted on the findings pertinent to interaction between several environmental variables affected by HVAC systems and their effect on Virus transmission. The results suggest that airflow velocity may interfere with the trajectories of large respiratory droplets and aerosols. Lower relative humidity provided suitable conditions for virus survival whereas higher temperatures increased aerosol formation, but were detrimental to virus survival. Suboptimal temperatures and humidity can compromise pathogen filtration functions in the nose, while proper use of HVAC functions can help preserve them. Transmission of SARS-COV-2 is not affected solely by the virus’s internal properties. Ambient conditions, whether natural or modified by HVAC systems can have a significant effect on the transmissibility and virulence of both the virus and virus-related sickness. The current infection prevention measures, such as social distancing, need to be revised in certain scenarios where natural ventilation or HVAC systems are involved. This will offer, hopefully, higher protection from infections with SARS-COV-2 and similar pathogens.